A Casa da minha Avó - Recuperação de um monte alentejano - Maria João Santinhos Trindade Pereira Latas (2019)
Motivated by a very personal concern, the current master's dissertation lays out a research process and ensuing development of an architectural proposal for the rehabilitation of a monte in Coastal Alentejo, likely built in the middle of the 19 th century. The building in question, an example of regional vernacular architecture, is abandoned and in ruin: both its rammed earth walls and the wooden structure that supports the roof have been, for years, in a state of decay that prevents its use. Our intent is that of restoring habitability to the house, balancing the current needs of a small home and the respect and wish to maintain the vernacular heritage. Through successive approaches to the house, which frame it in its site, its history, the social structure it bears and in the current paradigm of intervention on vernacular heritage, we lay the foundation to the knowing the object that will allows us to ponder and plan its future. We also believe that, more than a figure or collective, the vernacular house is the organic result of several conditionings and the empirical research to overcome them, materializing, without an author but with reasons, in a house-object. Thus, we find of extreme importance that the process included human elements, present along the text through memory reports which complete the image of the monte's past, guiding what can become its prospected development. Considering the intention of actually building the proposal here presented, the project uses data and drawings that correspond to a licensing phase, compounding what we hope is a well-integrated plan with the potential to contribute to maintain the vernacular heritage in southern Portugal.